Integrasi Teknologi Informasi dalam Pendidikan Akuntansi: Literature Review - Gita Rahmawati, Gita Rahmawati; Anis Windofiroh; Nikita Amelia; Liana, Liana; Ana Ngainurohmah (Penerbit Goodwood, 2024)
Purpose: This study aims to conduct a review of research on the integration of information technology in the scope of accounting education over the past 12 years.Research methodology: This study uses a systematic literature review method through a content analysis approach on 43 relevant journals. The research data is in the form of secondary data sourced from international journals and national journals for the period 2012-2024.Results: The results showed that the integration of information technology in accounting education is categorized into 4 aspects, namely (1) Aspects that impact information technology in accounting education, (2) Information Technology in General Accounting, (3) Integration of Information Technology in Accounting Education, (4) Development of Information Technology in Accounting Curriculum.Conclusions: Accounting education has undergone a significant transformation with the integration of information technology, such as Big Data, AI, and blockchain, to prepare students for digital challenges. Despite progress, challenges such as low digital literacy and limited internet access still hinder technology adoption. Updating the curriculum and IT infrastructure is essential to improve education quality and meet industry needs.Limitations: This research analyzes a range of literature related to the integration of information technology in accounting education published over the past 12 years, providing an up-to-date overview of developments in this area.Contribution: This research provides a systematic review and comprehensive categorization of the integration of information technology in accounting education over the past 12 years as a reference for future technology-based accounting curriculum development and learning practices.